Chronic compensated iron deficiency anaemia in a 12-year-old cerebral palsy child - Suresh, Jayasurya; Chandran, Nidheesh (International Journal of Contemporary Pediatrics, 2020)
A 12-year-old male child, known case of cerebral palsy (CP), presented as a case of severe anaemia with congestive heart failure to the paediatric casualty. The child was worked up for the same and investigations revealed chronic compensated iron deficiency anaemia. The child was treated with blood transfusions, anti-heart failure medications and was discharged on oral iron. Special care and follow up are required for the nutritional needs of CP children as often they are neglected leading to catastrophic presentations.